Use of [177Lu]Lu-DOTA-TATE in the treatment of gastroenteropancreatic neuroendocrine tumours: Results of a UK cost-effectiveness modelling study. (November 2021) - Glover, Matthew; Caplin, Martyn; Leeuwenkamp, Oscar R.; Longworth, Louise
Abstract: Aim: To evaluate the cost-effectiveness of [ 177 Lu]Lu-DOTA-TATE versus relevant comparators for the treatment of neuroendocrine tumours located in the gastrointestinal tract (GI-NETs) and the pancreas (P-NETs). Materials and methods: A three-state partitioned survival model was developed to perform a cost-utility analysis of [ 177 Lu]Lu-DOTA-TATE versus standard of care (high dose Octreotide LAR), everolimus and sunitinib. Effectiveness data for SoC, everolimus and sunitinib were obtained from published Kaplan–Meier survival curves. Given a lack of head-to-head effectiveness data, matching adjusted indirect comparisons (MAICs) were performed to population-adjust [ 177 Lu]Lu-DOTA-TATE survival data based on prognostic factors and derive estimates of relative effectiveness. Health state utilities were estimated from real-world evidence. Drug acquisition costs were taken from nationally published sources (BNF, NICE), and administration costs were based on treatment protocols in [ 177 Lu]Lu-DOTA-TATE studies, combined with nationally published unit costs (PSSRU, DoH reference costs). Incidence of adverse events were estimated using published sources. A discount rate of 3.5% was applied to both utilities and costs, and deterministic and probabilistic sensitivity analyses were performed. Costs were included from an NHS perspective and presented in 2017/18 GBP (and PPP Euros for base case). Results: In GI-NETs, the incremental cost-effectiveness ratio (ICER) of [ 177 Lu]Lu-DOTA-TATE compared to SoC and everolimus was £26, 528 (€27, 672) and £24, 145 (€25, 186) per QALY, respectively. In P-NETs, the ICER of [ 177 Lu]Lu-DOTA-TATE compared to SoC was £22, 146 (€23, 101) or £28, 038 (€29, 251) dependent on matched population, and £21, 827 (€22, 766) and £15, 768 (€16, 445) compared to everolimus and sunitinib, respectively. Conclusions: At a willingness to pay threshold of £30, 000, [ 177 Lu]Lu-DOTA-TATE is likely to be a cost-effective treatment option for GI-NET and P-NET patients versus relevant treatment comparators (NHS perspective). Highlights: A three-state partitioned survival model of GEP-NET patients was developed. Base case ICERs for [ 177 Lu]Lu-DOTA-TATE were under £30, 000 per QALY for all comparators. [ 177 Lu]Lu-DOTA-TATE is cost-effective for the treatment of GEP-NETs from a NICE perspective.